Penerapan Metode Drill Terhadap Peningkatan Kemampuan Dribbling Atlet SSB Putra Lubuklinggau - Arzalihac; Leo Charlie; Hengky Remora (Yayasan Darussalam Bengkulu, 2025)
This study aims to determine the application of the drill method to improve the dribbling ability of SSB Putra Lubuklinggau athletes. This research method uses a pre-experimental designs research method with a Pre-test and Post-test experimental design. Sampling in this study was purposive sampling because the samples taken were part of all the objects studied and were considered to be able to represent the population based on predetermined criteria, namely 18 athletes from 90 populations. Data collection techniques used observation, testing and documentation. The test instrument used by the researcher was a dribbling ability test. Data analysis used z-test statistics with a ZCount result of 4.530 which was greater than ZTable of 2.110. Based on these results, this study shows that the application of the drill method to improve the dribbling ability of SSB Putra Lubuklinggau athletes. The results of the pre-test and post-test showed an increase in dribbling ability, which was accompanied by a more uniform distribution of results among participants.